Long lasting effects of rTMS and associated peripheral sensory input on MEPs, SEPs and transcortical reflex excitability in humans - Tsuji, Tetsuya (Blackwell Science Inc, 2002)
We tested the effect of repetitive transcranial magnetic stimulation (rTMS) over the motor cortex on the size of transcortical stretch and mixed nerve reflexes. Fourteen healthy subjects were investigated using either 25 min of 1 Hz rTMS or 30 min of 0.1 Hz rTMS paired with electrical stimulation of the motor point of the first dorsal interosseous muscle (FDI). Following treatment, we measured the effect on the size of: (1) EMG responses evoked in FDI by transcranial magnetic stimulation (MEPs), (2) somatosensory evoked potentials (SEPs) evoked by ulnar nerve stimulation, and (3) transcortical stretch or electrically elicited reflexes. rTMS at 1 Hz reduced the amplitude of both MEPs and long latency reflexes by 20–30 % for about 10 min after the end of stimulation. Short latency reflexes were unaffected. SEPs were not studied, as it has been shown previously that they are also suppressed. rTMS at 0.1 Hz paired with motor point stimulation (interstimulus interval of 25 ms) increased the amplitude of the MEP and the cortical components of the SEP (N20/P25 and later peaks) for up to 10 min. Long latency reflexes were facilitated with the same time course. We conclude that rTMS over the motor cortex either alone or in conjunction with peripheral inputs can decrease or increase the excitability of the sensory and motor cortex for short periods after the end of stimulation. These changes affect not only MEPs and SEPs but also EMG responses to more ‘natural’ inputs involved in transcortical stretch reflexes.